(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Breast cancer is the most common cause of cancer death among women. Estrogen Receptor (ER), Progesterone Receptor (PR) and human epidermal growth factor receptor 2 (Her-2/ neu) status are used as an important prognostic marker for breast cancer. Objectives: The aim of this study was to evaluate ER and Her-2 in breast carcinoma among Bangladeshi women and to co-relate with other prognostic parameters. Materials and Methods: The study was carried out in a tertiary level hospital in Bangladesh during the period of January 2010 to December 2011. Total 100 histologically proved breast carcinoma cases were included in the study. Immunostaining for ER and Her-2/neu were carried out. Quick scoring of ER and expression of Her-2/neu were correlated with histomorphological parameters. Results: Among 100 cases 93 were ductal carcinoma and 07 were non ductal. Among all, 38% show ER positive (score- 3-8) while 62% are ER negative (score 0-2). Her-2/neu was over expressed in 30%, 22% were borderline and 48% were negative. There were inverse relationship between ER positivity and Her-2/neu overexpression. ER positivity was related with lower histological grade, while Her-2/neu overexpression was related with higher histological grade. Conclusions: ER positivity in Breast carcinoma patients in Bangladesh is lower in comparison to western literature while Her-2/neu overexpression rate is quite high like other Asian countries. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 7-13